Moroccan Local government's communication on Facebook : A simple dissemination or a dialogic communication. The case of Rabat-Salé-Kénitra municipalities' Facebook pages. - EL BELGHITI, Rokia; EL ABBADI, Abderrazak (Revue Internationale des Sciences de Gestion, 2024)
Like Moroccan public administrations, municipalities have been called upon by the state to redefine their relationship with citizens by considering them as active participants who need to be listened to and involved in local life. This implies, intuitively, a shift from communication whose main objective is transmission to communication that promotes interactivity and participation, through social networks like Facebook, if used in a dialogic manner. The objective of this study is therefore to first analyze to what extent the use of Facebook in the public communication of municipalities in the Rabat-Salé-Kénitra region aligns with a dialogic approach. Then, to propose concrete actions that will help that this usage translates into the creation and maintenance of relationships with citizens. To accomplish this, a case analysis of the Facebook pages of six municipalities in the region was conducted, based on the principles of dialogic theory. The results showed that these municipalities use Facebook primarily as a one-way communication tool rather than a true dialogic tool. Therefore, a guide for implementing dialogic communication strategies on Facebook was proposed to Moroccan municipalities.